As vivências dos bebês no berçário de uma escola municipal de educação infantil de Belo Horizonte: processos interacionais e a construção de sentidos em suas aproximações - Viviane Tolentino da Silva (2018)
This report describes the experiences constituted by a group of babies through the interactive dynamic established with the social environment, in the context of the nursery in a Municipal School of Infantile Education in Belo Horizonte, considering the way these interactional processes occur and the production of senses built in approximations. It was supported by the theoretical framework of Vygotsky and his collaborators, in the perspective of the theory of Historical-Cultural Psychology and the concept of experience (perezhivanie) (Vigotski, 1931/1996, 1933-1934 / 2010) to understand the children constitution as subject socio-historical-cultural and human formation. In order to find indicative responses to the central objective, a research with an ethnographic perspective was carried out in a group of 13 babies, aged 10 months to 1 year and 2 months, for six months, aiming at the daily nursery, the experiences and relationships established by children in this context. Data were obtained through filmed registrations, photographic records, field diary annotations and semi-structured interviews with adults. This resulted in a compendium of social actions of the babies, which revealed their ways of interacting when establishing their relationships in the educational space and the meanings woven in these encounters. For the analysis, an interface was made between the produced data and the delimited theoretical framework. Interpretations point to the potency of the nursery space, by promoting children's relationships at various times during the routine, by means of verbal and non-verbal expressions and by providing the experiences of the little ones. As results, we verified the dynamics of the unit {person | socio-cultural milieu}, constituted in a dialectical game in which the collective environment is transformed as the babies develop and all the participants of that environment also transform themselves. The development process of one of the babies was also evidenced: Icarus, of the one who needs more careful care for the one who cares. It concludes by emphasizing the implications of the knowledge produced on the experiences for the training of professionals in this collective environment of care and education. In this sense, the research brings subsidies to the pedagogical practice, contributing to the development of quality in the babies care in educational institutions